Burden of child and adolescent obesity on health services in England - Viner,RM; Kinra,S; Nicholls,D; Cole,T; Kessel,A; Christie,D; White,B; Croker,H; Wong,ICK; Saxena,S (Arch Dis Child, 2018)
OBJECTIVE: To assess the numbers of obese children and young people (CYP) eligible for assessment and management at each stage of the childhood obesity pathway in England. DESIGN: Pathway modelling study, operationalising the UK National Institute for Health and Care Excellence guidance on childhood obesity management against national survey data. SETTING: Data on CYP aged 2-18 years from the Health Survey for England 2006 to 2013. MAIN OUTCOME MEASURES: Clinical obesity (body mass index (BMI) >98th centile), extreme obesity (BMI >/=99.86th centile); family history of cardiovascular disease or type 2 diabetes; obesity comorbidities defined as primary care detectable (hypertension, orthopaedic or mobility problems, bullying or psychological distress) or secondary care detectable (dyslipidaemia, hyperinsulinaemia, high glycated haemoglobin, abnormal liver function). RESULTS: 11.2% (1.22 million) of CYP in England were eligible for primary care assessment and for community lifestyle modification. 2.6% (n=283 500) CYP were estimated to be likely to attend primary care. 5.1% (n=556 000) were eligible for secondary care referral. Among those aged 13-18 years, 8.2% (n=309 000) were eligible for antiobesity drug therapy and 2.4% (90 500) of English CYP were eligible for bariatric surgery. CYP from the most deprived quintile were 1.5-fold to 3-fold more likely to be eligible for obesity management. CONCLUSIONS: There is a mismatch between population burden and available data on service use for obesity in CYP in England, particularly among deprived young people. There is a need for consistent evidence-based commissioning of services across the childhood obesity pathway based on population burden.